PENGARUH PENERAPAN PSIKOEDUKASI TERHADAP TINGKAT KECEMASAN PADA PASIEN TB PARU RAWAT JALAN DI WILAYAH KERJA RSUD RUMAH SEHAT AMANAH HUSADA TAHUN 2024: THE EFFECT OF PSYCHOEDUCATION ON ANXIETY LEVELS IN OUTPATIENTS WITH PULMONARY TUBERCULOSIS IN THE WORKING AREA OF THE RUMAH SEHAT AMANAH HUSADA GENERAL HOSPITAL IN 2024 - Dewy, Tika Sari; Juniawan, Herdy; Sabila, Fatya (LPPM STIKes Bahrul Ulum Jombang, 2025)
One of the symptoms of pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterrium tuberculosis, which can cause psychological disorders such as anxiety. One therapy that can be applied to reduce anxiety in pulmonary tuberculosis patients is psychoeducation. This study aims to understand the impact of psychoeducation on anxiety in pulmonary tuberculosis patients The research design used a pre-experimental design with pretest and posttest on a single group. In this study, 20 pulmonary TB patients were selected using purposive sampling. The measurement tool used was the DASS-42 (Depression Anxiety Stress Scales) as a tool for measuring anxiety. Based on the research findings, it was found that before psychoeducation, most respondents experienced mild anxiety, and after psychoeducation, most participants were in the mild anxiety category. Statistical analysis using the Wilcoxon test found a p-value (Sig.2-tailed) of 0.000000 (